Pengaruh Penetapan Harga terhadap Kinerja Hotel di Kota Bandung Peran Kepuasan terhadap Traveloka Sebagai Variabel Mediasi - Muhammad Hari; Rahmat Priyanto (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2026)
Hotel dependency on digital platforms such as Traveloka continues to increase, whether in setting prices, attracting customers, or managing operations. This study aims to analyze the effect of pricing strategies on hotel performance in Bandung City, with hotel satisfaction as a mediating variable. The research employs a quantitative method using Structural Equation Modeling (SEM) with a Partial Least Squares (SmartPLS) approach. Data were collected from 30 respondents who are hotel employees using the Traveloka platform. The research instrument was developed based on theoretical indicators and tested through outer loading analysis, validity, reliability, multicollinearity, path analysis, and mediation testing. The results indicate that pricing strategies have a positive and significant effect on hotel satisfaction and company performance. Hotel satisfaction also significantly influences company performance. Furthermore, the mediation test shows that hotel satisfaction partially mediates the relationship between pricing strategies and company performance (p = 0.019). The pricing strategies implemented through Traveloka not only have a direct impact on hotel performance but also an indirect effect through increased partner hotel satisfaction.